A user authentication scheme based on identity-bits commitment for wireless sensor networks - Jamil N.; Sameon S.S.; Mahmood R. (2023)
Wireless sensor networks have received a great attention since they emerged as new ways of communicating and distributing information in wireless network. However the security aspect of wireless sensor network remains an issue, namely authentication, key management and secure localization. Since the communication of wireless sensor is on broadcast basis, researchers are focusing on how to design an efficient authentication scheme since the data might lost during the transmission and this is crucial for entity authentication prior the actual communication. Entity or user authenticity is important to avoid forgery and replay attack. This paper will focus on authentication by investigating three authentication schemes based on user authentication for Wireless Sensor Network. We identify their weakness and we finally introduce a new scheme which is based on identity-bits commitment for authentication that overcomes problems identified in studied schemes. A basic security analysis is followed to support the strength of the scheme in a real deployment. 2010 IEEE.